KORELASI ANTARA MOTIF HIAS SONGKET DAN UKIRAN KAYU DI PROPINSI SUMATERA BARAT - Minarsih, Minarsih (Humanus, 2013)
This study aims to reveal the relation between carving and weaving products designed by west Sumatran craftsmen. The observation is made based on the motives used in the two products, including structure, position, repetition, and color arrangement of the patterns. The findings reveal that 42 – 65 % carving motives have the same naming in Pandai Sikat weave, while small number of old carving pattern appear in new design. The same motives were also found in weaving products of Kubang (33%) and Silungkang (25%).Based on this finding, it can be concluded that some weaving motives influence the carving motives and vice versa. Key words: handicraft, design, motive, carving, weaving